Class 1 integrons and multiple mobile genetic elements in clinical isolates of the Klebsiella pneumoniae complex from a tertiary hospital in eastern China - Wang, Lan; Zhu, Mei; Yan, Chunxia; Zhang, Yanfang; He, Xuying; Wu, Lin; Xu, Jiefeng; Lu, Junwan; Bao, Qiyu; Hu, Yunliang; Xu, Teng; Liang, Jialei (Frontiers in Microbiology, 2023)
The emergence of highly drug-resistant Klebsiella species, especially K. pneumoniae, has become a major public health challenge. In this work, we employed whole-genome sequencing and various bioinformatic methods to investigate the species and sequence type (ST) diversity of clinical Klebsiella isolates and to characterize the prevalence and structure of resistance gene-related class 1 integrons. Species identification based on average nucleotide identity (ANI) showed that the 167 isolates belonged to four species: K. pneumoniae, K. variicola subsp. variicola, K. quasipneumoniae and K. aerogenes. Thirty-six known and 5 novel STs were identified in K. pneumoniae, and 10 novel STs were identified in K. variicola subsp. variicola. Class 1 integrase genes were found in 57.49% (96/167) of the isolates, and a total of 169 resistance gene cassettes encoding 19 types of resistance genes, including carbapenem resistance genes (blaIPM-4) and class D β-lactamases (blaOXA-1 and blaOXA-10), were identified. Among the 17 complete genomes, 29 class 1 integrons from 12 groups were found, and the members of 1 group were all encoded on chromosomes. Interestingly, we identified one plasmid (pKP167-261) carrying two copies of an approximately 19-kb IS26-Int1 complex resistance region that contains an integron and a multidrug resistance gene fragment in the form of a tandem repeat. New structures related to mobile genetic elements (MGEs), especially two copies of the IS26-Int1 complex resistance region as found in one bacterium, indicate the great importance of deeply exploring the molecular mechanisms of bacterial multidrug resistance.